2014
DOI: 10.1016/j.aim.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Semisimple Hopf actions on commutative domains

Abstract: Abstract. Let H be a semisimple (so, finite dimensional) Hopf algebra over an algebraically closed field k of characteristic zero and let A be a commutative domain over k. We show that if A arises as an H-module algebra via an inner faithful H-action, then H must be a group algebra. This answers a question of E. Kirkman and J. Kuzmanovich and partially answers a question of M. Cohen.The main results of this article extend to working over k of positive characteristic. On the other hand, we obtain results on Hop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 11 publications
(11 reference statements)
2
82
0
Order By: Relevance
“…This work contributes to the field of noncommutative invariant theory in the sense of studying quantum analogues of group actions on commutative k-algebras. Here, we restrict our attention to the actions of finite quantum groups, i.e., finite dimensional Hopf algebras, as these objects and their actions on (quantum) k-algebras have been the subject of recent research in noncommutative invariant theory, including [8], [10], [16], [18], [27], [29], [34], [35], [37]. The two important classes of finite dimensional Hopf algebras H are those that are semisimple (as a k-algebra) and those that are pointed (namely, all simple H-comodules are 1-dimensional).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work contributes to the field of noncommutative invariant theory in the sense of studying quantum analogues of group actions on commutative k-algebras. Here, we restrict our attention to the actions of finite quantum groups, i.e., finite dimensional Hopf algebras, as these objects and their actions on (quantum) k-algebras have been the subject of recent research in noncommutative invariant theory, including [8], [10], [16], [18], [27], [29], [34], [35], [37]. The two important classes of finite dimensional Hopf algebras H are those that are semisimple (as a k-algebra) and those that are pointed (namely, all simple H-comodules are 1-dimensional).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we have many choices of what one could consider to be a quantum k-algebra, but from the viewpoint of classical invariant theory and algebraic geometry, the examination of Hopf actions on commutative domains over k is of interest. Since the classification of semisimple Hopf actions on commutative domains over k is understood by the work of the authors [18], the focus of this article is to classify finite dimensional non-semisimple Hopf (H-) actions on commutative domains over k, particularly when H is pointed.…”
Section: Introductionmentioning
confidence: 99%
“…By Proposition 2(3) one concludes that H has to be cocommutative, and hence a group algebra. Their key result of [3] extending [4] is the following: As a consequence from this Proposition and the reduction process to fields of positive characteristic, as described in sections 2 and 3, one deduces: …”
Section: Reduction To Hopf Algebras Over Finite Fieldsmentioning
confidence: 94%
“…Note that when the action of H preserves the standard filtration of A n (k), Theorem 4.1 can be deduced from [EW1,Proposition 5.4], since the associated graded algebra gr(A n (k)) is a commutative domain. Our main achievement in this paper is to eliminate this assumption.…”
Section: Introductionmentioning
confidence: 99%
“…Let k be an algebraically closed field of characteristic zero and H a semisimple Hopf algebra over k. In [EW1,Theorem 1.3], two of the authors showed that any action of H on a commutative domain over k factors through a group action. The goal of this paper is to extend this result to Weyl algebras.…”
Section: Introductionmentioning
confidence: 99%